Symbolic content diffusion and cultural dialogue on the example of the European Martial Arts Committee – international expert board, 2010–2020 - Georgiy Korobeynikov; Wojciech Czarny; Wojciech J. Cynarski (Sport i Turystyka, 2022)
Background. Fighting Arts are interesting from the perspective of their institutionalisation, organisational development, globalisation and glocalization, and also as vehicles of cultural dialogue.